Penggunaan Media Permainan Pohon Angka dalam Menstimulus Kemampuan Mengenal Angka Anak Usia 4-5 Tahun di Pos PAUD Harapan Bangsa Desa Wonosari - Rokhmah, Nur; Hambali , Habib (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
Children aged 0 to 5 years are the golden age. This period is an ideal time for children to seek, learn and acquire basic concepts that will affect the child's life in the future. Children are small human beings who have potential that still needs to be developed. Children have certain characteristics that are unique and not the same as adults, they are always active, dynamic, enthusiastic and curious about what they see, hear, feel as if they never stop exploring and learning. Egocentric children have natural curiosity, are social beings, unique, rich in fantasy, have short attention spans and are the most potential period for learning.Early childhood education is the provision of efforts to stimulate, nurture, and provide learning activities that will produce abilities and skills in the child, early childhood education, especially PP (POS PAUD) needs to provide a variety of interesting, meaningful, effective, and enjoyable experiences. fun that can develop various aspects of development which include cognitive, language, social, physical motor, and art.